Risk for eating disorders, anxiety, depression and other emotions related to publicitary images exposure. - Jiménez-Cruz, Blanca Elizabeth (Anales de Psicología / Annals of Psychology, 2010)
In order to explore the anxiety and depression levels, the emo-tions produced by images taken from media and risk for eating disorderes, a total of 376 women participated in this test-postest study, 140 of the participants were exposed to thin women images, 127 to overweight women images and 109 to women exercising or eating in a “healthy” way images. All participants were evaluated with the Eating Attitude Test (EAT-40), the State-Trait Anxiety Inventory (STAI), the Axelrod Adjec-tive Checklist and an Emotion Questionary. Results revealed that depres-sion and anxiety levels increased in all participants at risk for eating disor-ders after exposure to images, but levels decreased for the rest of the participants. However, participants exposed to thin women images re-ported more negative emotions towards their bodies than those who were exposed to overweight women images. Findings suggest that the ideal transmitted through media promote disgusting emotions in young women, which may put them at risk for eating disorders.